Carbon-based microfibers catalysts for methanol production by CO2 hydrogenation. - Jiménez-Gómez, María del Rocío; Ruiz-Rosas, Ramiro Rafael; Rosas-Martínez, Juana María; Rodríguez Mirasol, José; Cordero-Alcántara, Tomás (My University, 2025)
The hydrogenation of COpromising and sustainable pathway for the production of methanol, offering a viable alternative to conventional fossilbased methods. Structured catalysts with Cu/ZnO metal phases are typically used in methanol synthesis.
Keywords: Fibras de carbono; Metanol (Combustible); CO2; H2; Nanofibers; Methanol